Novel predation opportunities in anthropogenic landscapes - Fleming, P.; Bateman, Bill (Elsevier Ltd., 2018)
Novel ecosystems (‘emerging ecosystems’) result when species occur in combinations and relative abundances that have not occurred previously within a given biome, due to deliberate or inadvertent human agency. Humans have changed the environment through disturbance, physical structures or additional resources. Many vertebrate predators inhabit cities, towns and other places that humans have built or altered, and make use of these anthropogenic niches. These predators range in size from bats swarming around lamp posts, to leopards stalking domestic animals in the heart of cities. In this essay, we describe four scenarios where predators opportunistically make use of anthropogenic niches. First, humans are surrounded by animals, including synanthropic rodents and birds, livestock and pets, that can be novel prey for opportunistic predators. Second, feeding on prey concentrations created through anthropogenic niches increases their hunting efficiency, by reducing both search and commute times. Third, anthropogenic environments create novel situations such as thermals and artificial lighting that advantage some predators, increasing their capture success. Finally, many predators have developed novel hunting strategies to make the most of opportunities in anthropogenic environments that can lead to greater hunting success. We give examples of these four scenarios and have developed a conceptual model that captures the common mechanisms relevant to each, with predictions for how these can be explored further in future studies. Predators exploiting anthropogenic niches can experience greater ease of hunting, decreased search effort and/or increased capture success. Consequently, these animals experience many physiological and reproductive benefits over conspecifics that do not make similar use of anthropogenic niches, ultimately benefitting from living alongside humans.